Love Across Borders: Understanding Intercultural Communication in Japanese-Balinese Marriages - Dalimunthe, Maulana Andinata; Dewi, Ni Made Ana Surya (Universitas Pendidikan Nasional, 2023)
Bali Island is an island that has art, culture and natural beauty. The majority of the population inhabiting the island of Bali are Balinese people who adhere to the Hindu religion. A tourist destination in Bali that is well known to domestic tourists and tourists from various countries is Peliatan Village. An amalgamation marriage is a marriage that takes place between two people of different ethnicities. This meeting between local Balinese residents and foreign tourists is a factor in the occurrence of an amalgamation marriage. This Japanese citizen who married an ethnic Balinese man adapted between cultures to maintain their interactions and relationships with everything in their new environment. This research was conducted using qualitative methods and used descriptive research. The main data collection techniques are observation and interviews. The aim of this research is to determine intercultural communication patterns in the process of social interaction in amalgamation marriages. Based on the results of data analysis, thatThe process of intercultural communication patterns in husband and wife couples carrying out amalgamation marriages in Peliatan village found that there were several difficulties in carrying out social interactions experienced by Japanese citizens to get used to their new environment, and there were difficulties communicating at the beginning due to different languages.